2000
DOI: 10.1038/sj.ejcn.1601011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an energy and micronutrient supplement on iron deficiency anemia, physical activity and motor and mental development in undernourished children in Indonesia

Abstract: Objectives: This paper reports the effects of an energy and micronutrient supplementation on mental and motor development, activity and behavior under natural conditions of children classi®ed as iron de®cient anemic and iron replete. Design: Children were randomly assigned to two different nutritional supplements: (1) 12 mg iron either 1171 or 209 kJ; (2) 104 kJ 0 iron. Treatment lasted for 6 months. Setting: The sites were six tea plantations in Pangalengan, West Java. Subjects: Eighteen anemic subjects (hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 16 publications
3
38
1
9
Order By: Relevance
“…The results observed in this study are in agreement with previous research that has shown an improvement in cognitive measures in infants (Oski & Honig, 1978;Walter et al, 1983;Driva et al, 1985;Idjradinata & Pollitt, 1993;Harahap et al, 2000;Lozoff et al, 2003), preschoolers (Pollitt et al, 1983(Pollitt et al, , 1986Seshadri & Gopaldas, 1989;Soewondo et al, 1989;) and school age children (Seshadri & Gopaldas, 1989;Bruner et al, 1996;Lynn & Harland, 1998) after treatment with iron. This study's findings advances our understanding in a number of ways particularly in delineating the type of attentional processes affected by IDA.…”
Section: Discussionsupporting
confidence: 83%
“…The results observed in this study are in agreement with previous research that has shown an improvement in cognitive measures in infants (Oski & Honig, 1978;Walter et al, 1983;Driva et al, 1985;Idjradinata & Pollitt, 1993;Harahap et al, 2000;Lozoff et al, 2003), preschoolers (Pollitt et al, 1983(Pollitt et al, , 1986Seshadri & Gopaldas, 1989;Soewondo et al, 1989;) and school age children (Seshadri & Gopaldas, 1989;Bruner et al, 1996;Lynn & Harland, 1998) after treatment with iron. This study's findings advances our understanding in a number of ways particularly in delineating the type of attentional processes affected by IDA.…”
Section: Discussionsupporting
confidence: 83%
“…Nutritional and health factors such as iron deficiency anemia and stunting influence both motor development (5-9) and motor activity (3,(10)(11)(12)(13)) and these in turn influence each other with effects on children's ability to explore the environment and caregiver behavior. Motor activity is highly dependent on motor development.…”
Section: Introductionmentioning
confidence: 99%
“…More than 30 years of research revealed the negative impact of IDA on Intelligence, behavior, psychomotor, Social, cognitive performance, neurophysiologic and metabolic functions of brain [11]. Studies proved IDA negatively influence scores on tests of intelligence (6-15 points lower) [9] reduced motor activity [14][15][16] developmental delay [16] with disturbed socio-emotional behavior like irritability, decreased attention span and emotional responsiveness [10]. It is hypothesized that during infancy particularly, rapid development leads to peak metabolic activity of brain making it more liable to deficiencies of substrates required for metabolism [9,13,17,18].…”
Section: Discussionmentioning
confidence: 99%